Musculoskeletal Disorders in Students During Covid-19 Pandemic: Literature Review - Tambun, Madschen Sia Mei Ol Siska Selvija (Journal of Engineering, Technology, and Applied Science (JETAS), 2021)
Pandemi Covid-19 telah menjadi perhatian di seluruh dunia. Kebijakan dalam rangka pencegahan penyebaran virus seperti pembelajaran online juga diberlakukan pada mahasiswa. Mahasiswa yang mengikuti pembelajaran online mayoritas mengalami keluhan musculoskeletal pada bagian tubuh seperti leher, bahu, punggung dan pinggang. Metode penelitian ini adalah literatur review dengan menghasilkan 14 artikel penelitian. Keluhan musculoskeletal apabila tidak ditindaklanjuti maka akan berdampak jangka panjang seperti gangguan tidur dan kecacatan. Musculoskeletal Disorders in Students During Covid-19 Pandemic: Literature Review Abstract: COVID-19 pandemic has become an international concern. Policies to prevent the spread of disease, such as learning from home, are applied to university students. The majority of students who take online learning experience musculoskeletal complaints in body parts such as the neck, shoulders, back and waist. This research method is literature review by producing 14 research articles. Musculoskeletal complaints if not followed up will have long-term impacts such as sleep disturbances and disability. Keywords: Covid-19, Muscuoskeletal Disorders, Online Learning, Student.